Analisis kesulitan matematis mahasiswa berdasarkan teori pemrosesan informasi menggunakan media kahoot! - Ikhsana, Aulia; Anwar, Lathiful; Sisworo, Sisworo (IKIP Siliwangi, 2024)
This approach focuses on students' thinking procedures. This study aims to describe the obstacles of students in innovative learning using Kahoot! in solving mathematics problems according to Robert Gagne's theory. Information processing theory explains how information is received, processed, and stored in memory, where difficulties can arise at each stage, such as limited short-term memory capacity and problems in encoding information into long-term memory. This research method uses a qualitative descriptive approach, with data collection through observation, interviews, and group discussions. The subjects in this study were all OFF G mathematics students in semester 1 at Malang State University in the 2024/2025 academic year, totaling 30 students. The data obtained in this study were written tests in the form of questions on the material of composition functions and inverse functions and interview guidelines. The research results indicate that: (1) students experience obstacles related to understanding each procedure for solving mathematics problems, concepts, procedures, or principles for working on mathematics problems, and (2) the trigger for students' limitations in learning mathematics is the lack of motivation from students to access information that they do not understand.